Pocket welding guide : a guide to better welding. (Hobart Institute of Welding Technology, 2013)
This newly updated edition features overviews of all welding processes, examples of good and bad weld beads, causes and cures of common welding problems, and guidelines for the identification of metals and calculating filler metal consumption. Additional topics found in the book include oven storage and reconditioning of filler metals, welding symbols, shielding gases and their uses, AWS filler metal classifications and comparative indices, GMAW welding parameter, complete listing of filler metals with operating ranges, filler metal selector guide for welding ASTM steels, troubleshooting guides for semiautomatic wire and equipment, welding terms and definitions, metric conversion tables, and more.